Simultaneous bilateral midshaft clavicle fractures with unilateral dislocation of the acromioclavicular joint: A case report. Issue 21 (May 2017) - Dong, Dong; Yu, Mingyang; Gu, Guishan
Abstract: Rationale: Simultaneous bilateral mid-clavicle fracture with unilateral dislocation of the acromioclavicular (AC) joint is an extremely rare injury combination. Patient concerns: Herein, we report a case of polytrauma in a 42 years old female following a road traffic accident. Diagnoses: The radiographs showed the fractures in bilateral middle third of the clavicle and AC joint dislocation of left shoulder. Interventions: The patient was treated with a 5-hole locking hook plate to stabilize the left AC joint and a shortly reconstruction plate to fix the left clavicle. Moreover, another 6-hole truncated anatomic reconstruction plate was used to fix the fracture of the right clavicle. Outcomes: At the 1-year follow-up, the patient had excellent range of motion and functional outcomes. Lessons: It is important to achieve stability and aim for excellence in terms of full shoulder function in this rare combination injury.